2018
DOI: 10.1111/bjdp.12220
|View full text |Cite
|
Sign up to set email alerts
|

Parenting differentially influences the development of boys' and girls' inhibitory control

Abstract: Effortful control (EC) has important implications for children's development. While both child sex and parenting are related to child EC, and while a literature shows early sex differences in children's responses to care, interactions between care and child sex in predicting EC are not well understood. We therefore examined associations between child sex and early caregiving as predictors of children's development of a specific aspect of EC, inhibitory control (IC). A community sample of 406 three-year-old chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
21
1
2
Order By: Relevance
“…Parenting behaviours such as sensitivity and cognitive stimulation shape early development by facilitating healthy cognitive and regulatory development (Cabrera et al, 2011;Mills-Koonce et al, 2010). Moreover, research has demonstrated support for the association between high-quality maternal-child interactions and child executive functions, such as IC (Bernier et al, 2010), especially parental sensitivity in the toddler years (Amicarelli, Kotelnikova, Smith, Kryski, & Hayden, 2018;Kochanska, Murray, & Harlan, 2000).…”
Section: Role Of Maternal Warmth In Development Of Inhibitory Controlmentioning
confidence: 99%
“…Parenting behaviours such as sensitivity and cognitive stimulation shape early development by facilitating healthy cognitive and regulatory development (Cabrera et al, 2011;Mills-Koonce et al, 2010). Moreover, research has demonstrated support for the association between high-quality maternal-child interactions and child executive functions, such as IC (Bernier et al, 2010), especially parental sensitivity in the toddler years (Amicarelli, Kotelnikova, Smith, Kryski, & Hayden, 2018;Kochanska, Murray, & Harlan, 2000).…”
Section: Role Of Maternal Warmth In Development Of Inhibitory Controlmentioning
confidence: 99%
“…Em relação Ă  categoria "construtos gerais de parentalidade", os fatores latentes de qualidade parental (Meuwissen & Englund, 2016;Rolan et al, 2018;Sulik et al, 2015) e parentalidade positiva (Amicarelli et al, 2018;Blair et al, 2011;Smith et al, 2013) estiveram associados com uma melhor habilidade executiva, enquanto os componentes de parentalidade negativa apresentaram relaçÔes inversas ao desempenho das FEs em todos os estudos (Blair et al, 2011;Devine et al, 2016;Hughes & Devine, 2017;Smith et al, 2013). Quanto Ă  categoria "prĂĄticas de cuidado e afetividade parental", a sensibilidade se mostrou associada positivamente Ă s FEs em parte dos estudos (Blair et al, 2014;Gueron-Sela et al, 2017;Holochwost et al, 2018;Kok et al, 2014;Lucassen et al, 2015;Spruijt et al, 2018); porĂ©m, Cheng et al (2018), em uma amostra de crianças chinesas de seis a 38 meses, Para a variĂĄvel hostilidade, Lam et al (2018) observaram relaçÔes negativas com as FEs, tanto para hostilidade materna, quanto paterna.…”
Section: Resultados Dos Estudosunclassified
“…Notably, Met/Met boys in positive parenting environments had higher levels of parent‐reported IC (Sulik et al, ). Future research should explore what environmental influences, such as parenting or early adversity, interact with COMT genotype to predict unexplained variance in trajectories of IC development (Amicarelli, Kotelnikova, Smith, Kryski, & Hayden, ; Moilanen, Shaw, Dishion, Gardner, & Wilson, ). Similarly, initial work has also demonstrated a link between COMT , IC, and internalizing psychopathology (Sulik et al, ), in line with other work linking temperament, IC development, and anxiety specifically (Troller‐Renfree et al, ).…”
Section: Discussionmentioning
confidence: 99%